2009
DOI: 10.1590/s1677-55382009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Can infundibular height predict the clearance of lower pole calyceal stone after extracorporeal shockwave lithotripsy?

Abstract: PURPOSE: To evaluate the efficacy of extracorporeal shock wave lithotripsy (SWL) on lower calyceal calculi in relation to the renal anatomical factors and determine which of these factors can be used to select patients who will benefit from SWL. MATERIAL AND METHODS: We analyzed retrospectively 78 patients with single radiopaque lower calyceal stones treated with SWL. The patients were evaluated 3 months after lithotripsy with a simple abdominal X-ray and a kidney ultrasound scan. The success of the treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The congenital anomalies of upper urinary tract occur in almost 10% of all urinary system malformations. Calculi in lower calyceal group represent more cases in almost 24%–44% of all calculi requiring treatment because of longer stasis of urine in lower infundibulum [6] , [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The congenital anomalies of upper urinary tract occur in almost 10% of all urinary system malformations. Calculi in lower calyceal group represent more cases in almost 24%–44% of all calculi requiring treatment because of longer stasis of urine in lower infundibulum [6] , [9] .…”
Section: Discussionmentioning
confidence: 99%
“…In present study, we found more percentage of extra-renal pelvis (21.9%) in comparison to previous authors ( Table 1 ). Clinically, the extra-renal pelvis is roomier and more convenient to explore during nephron sparing surgery and partial nephrectomy than the intra-renal pelvis because it provides larger surface area away from the renal vasculature for safe surgery but the drawback is that the larger pelvic space aggravates accumulation and stasis of urine predisposing formation of renal calculi [9] . A distended renal pelvis and collecting system facilitate the puncture, placement, and maneuvering of the endourologic instruments and by providing a larger fluid chamber around a stone, enhance the efficacy of ESWL [11] , [12] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…This finding might explain the variability of the results in different reports. Arzoz-Fabregas et al [11] reported that lower infundibular height was the only anatomical factor that could be a good measurement tool for deciding which patients with lower calyceal lithiasis would benefit from SWL treatment. They suggested that patients with a lower infundibular height <22 mm have a good outcome from lithotripsy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Other studies have shown that a shorter infundibular length (<22 mm) as well as larger stone size (>10 mm) and burden can decrease stone free rates. [ 3 4 5 8 9 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that treatment of lower pole stones (LP) stones has a lower stone free rate (SFR) than other renal or ureteral stones due to the LP anatomy. [ 3 4 5 ]…”
Section: Introductionmentioning
confidence: 99%